Pengembangan Potensi Ekonomi dan Identifikasi Sektor Unggulan dalam Pembangunan Daerah di Kabupaten Magetan dan Kabupaten Ngawi - Vika Amalia Febriyanti; Wiwin Priana; Muhammad Wahed (Jurnal Syntax Admiration, 2024)
Regional economic development is the process by which local governments and their communities work together to manage available resources. It is expected that this development will drive economic growth in the area by creating new jobs and thus increasing per capita income. Thus, the local economy will develop. This study aims to identify the leading sectors in Magetan Regency and Ngawi Regency, and evaluate whether there are differences between the leading sectors in the two regencies. In addition, this study also aims to understand the role of leading sectors in the development of economic potential in the two districts. The population of this research is the economic sectors in Magetan Regency, Ngawi Regency, and East Java Province in the 2017-2022 period. The research method is based on a quantitative approach using LQ, Shift Share, and Klassen Typology analysis methods. The results showed that Magetan and Ngawi Regencies in the same LQ calculation had 7 leading sectors. The economic sector received positive results in all three components in the SS calculation there are 7 sectors in Magetan Regency while Ngawi Regency has only 6 sectors. And in the Klassen Typology analysis there are 4 economic sectors that qualify for quadrant 1 in Magetan Regency while Ngawi Regency has only 3 economic sectors. The sectors that have experienced significant positive growth in the three analyses include water supply, waste management, landfills and recycling, education services, health services and social activities.